Desenvolvimento de um aplicativo de guia de programação de canais de TV digital - Fabrício, Marcos André [UNESP] (2015)
This paper presents the development of a similar application to the Electronic Program Guide available on digital TV, by which it becomes possible to view, in real time, the program schedule organized by categories, in addition to enabling access to information about the programs and schedules. The Cloud Guide application, proposed in this paper, has its development based on web tecnologies with cloud computing, HTML5 and CSS, where a database APIs and feed application services, which in turn displays information to the viewer on programs available as name, channel, genre, agre rating, start time, end time, and abstract images of the film. This type of application development and enable rapid deployments and upgrades, unlimited information to the viewer, possibility to better understand the viewer profile based on what he seeks and even the monetization of products and services offered